MODIFIKASI SISTEM DESTILASI MINYAK ATSIRI DAUN SIRIH (PIPER BETLE LINN) DENGAN PENERAPAN VOLUME AIR REBUSAN KONSTAN - Widodo -; Agus Prasetya (ASEAN Journal of Systems Engineering, 2014)
Most of the cultivation of essential oils, done with the process of distillation such as water distillation systems, direct steam distillation and steam boiler distillation. And was developed on a small/medium scale industry throughout the archipelago.In the process of water distillation, the flow rate and level of oil transport are determined by the ratio of raw materials volume versus distillations water volume. Later on, affected by the steam temperature as well. Both were influenced by the vapor pressure inside the boiling tank, which will determine the level of vapor saturation of oil to be transported.Modifiying the distillations process with applying a control tank to avoid decreasing of distillations watter during the process, with increasing the steam pressure, has successfully improove the oil transports until its optimum rates.By ratio of 4:1 with increasing steam pressure up to 0.3 kgf/cm2, has affecedt to incresing the steam temperature and the rate of oil transport, there for iproofing the yield from 0.44% to 0.71% by total of 80 l water condensate.